Treatment of relapsed urothelial bladder cancer with vinflunine: real-world evidence by the Hellenic Genitourinary Cancer Group - Pistamaltzian, Nikolaos (Anticancer Drugs, 2016)
Relapsed urothelial cancer represents an unmet medical need. Vinflunine is a third-generation antimicrotubuline inhibitor and is currently the only approved drug for second-line treatment across the European Union. We conducted a retrospective analysis assessing the efficacy and safety of vinflunine in 71 Greek patients with relapsed urothelial cancer who were treated between 2005 and 2014. An overall 84% of our patients received vinflunine as second-line treatment, 77% had a performance status of Eastern Cooperative Oncology Group scale 0 or 1, and 30% had liver metastasis at the time of vinflunine administration. A median of four cycles of vinflunine were administered (range 1–16). The most common reported adverse events were constipation, fatigue, and anemia. Median progression-free survival was 6.2 months (95% confidence interval: 4.4–8.8) and overall survival was 11.9 months (95% confidence interval: 7.4–21). Two patients (3%) achieved a complete remission, seven a partial remission (10%), and 22 (31%) had stable disease according to an intention-to-treat analysis. Hemoglobin level less than 10 g/dl and Eastern Cooperative Oncology Group performance status greater than 1 were independent adverse prognostic factors. Stratification according to the Bellmunt risk model was also associated with progression-free survival and overall survival in our population. Vinflunine appears to be a safe and effective treatment modality for relapsed urothelial cancer. More effective therapies and more accurate prognostic algorithms should be sought.